2014
DOI: 10.1103/physrevb.90.045122
|View full text |Cite
|
Sign up to set email alerts
|

Collective excitations in the metallic triangular antiferromagnetPdCrO2

Abstract: We report a combined Raman-scattering and electron spin resonance (ESR) study of the metallic triangular compound PdCrO 2 along with lattice dynamic calculations. Our Raman data reveal (i) an exponential increase of the 706 cm −1 A g mode involving the out-of-plane motions of the oxygen atoms and (ii) electronic Raman scatterings whose scattering rate is strongly suppressed as the temperature approaches T N = 37.5 K. The temperature dependence of the ESR linewidth is described by a critical broadening H pp (T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…So far, the advanced electronic structure theory beyond DFT was mainly utilized to achieve agreement with available experimental findings. However, it reveals also new insight into the crucial coupling of itinerant electrons with dominant Pd character and localized Cr electrons 31,36 .…”
Section: Coupling Of Localized and Itinerant Electronsmentioning
confidence: 99%
“…So far, the advanced electronic structure theory beyond DFT was mainly utilized to achieve agreement with available experimental findings. However, it reveals also new insight into the crucial coupling of itinerant electrons with dominant Pd character and localized Cr electrons 31,36 .…”
Section: Coupling Of Localized and Itinerant Electronsmentioning
confidence: 99%
“…along with Raman active phonon wavenumbers taken from [24] for PdCoO2, PtCoO2 and PdRhO2, and [25] for PdCrO2. Infrared active phonon wavenumbers have also been calculated and, for PdCrO2, measured in the cited papers.…”
Section: Crystal Structure and Optical Phonon Energiesmentioning
confidence: 99%
“…Further transport measurements have shown the effect of the short-range order on the Hall and Nernst effects [46]. Raman and electron spin resonance (ESR) measurements [47] have also shown evidence for inter-layer hoppings along the c-axis and a reconstruction of electronic bands on approaching T N . Recent ARPES [12] measurements in the antiferromagnetic phase showed that the measured spectra can be explained by an intertwined excitation consisting of a convolution of the charge spectrum of the metallic Pd layer and the spin susceptibility of the Mott insulating CrO 2 layer.…”
Section: Resultsmentioning
confidence: 98%